IbM Penerapan Sistem Pentanahan di Kelurahan Agrowisata: - Tanjung, Abrar; Hamzah; Arlenny (FLEKSIBEL: Jurnal Pengabdian Masyarakat, 2022)
The grounding system is a way of overcoming disturbances caused by natural, internal and human error disturbances on an object with an electrical system through a conductor to the earth using a grounding electrode. Grounding electrodes are made of metal materials such as copper, iron, nickel, gold and other metal materials, but most of the materials used are made of copper, because they have high heat resistance and good conductivity. Standardization is a reference or provision in the use of materials and equipment in the grounding system. The standardization used is the Indonesian National Standard (SNI) in the electricity sector and the PLN standard (SPLN). The Agrotourism Village is a division of the Palas Village, Rumbai District in 2016. The activity partners in this case the Agrotourism Village community often experience disturbances and damage to electrical and electronic equipment and components caused by natural disturbances such as lightning strikes and short circuits. Based on the results of the discussion, partners obtained in knowing and understanding about the Grounding System after counseling by 90%, Partners knowing and understanding about whether you know and understand the General Requirements for Electrical Installation (PUIL) 2011 by 75%, Partners know and understand about materials and electrical equipment according to the Electrical Standards (SNI) after counseling is 85%, activity partners know and understand about whether you know and understand about the installation of a grounding system after counseling is 75%, activity partners know and understand whether you know and understand about the use of materials and equipment for the Grounding System after counseling by 90%.